Colour Preference, Size Discrimination and Motor Performance of Children 7 - 10 Years Old - Adeyanju, S. A.; Adeyanju, L. A. (2014)
This investigation was designed to determine the colour preference; assess size discrimination and motor performance ability of children 7-10 years old. Ninety school children (45 males and 45 females) with a mean age of 8.50 (SD + 2.3) were subjects for the study. Subjects reacted to a questionnaire relating to colour preference and colour charts. They also participated in a catching test to assess the motor performance ability. Data collected were analysed using descriptive statistics and a two-way analysis of variance. Results indicated that colour preferences of subjects were sex biased with males preferring red colour and females blue colour. Size discrimination ability was fairly well established among subjects. ANOVA indicated a significant effect for the age and sex factors for catching. It was concluded that red and blue colours were preferred by male and female subjects respectively and that the highest level of catching skill is well established at age 10.